Proses Asuhan Gizi Terstandar pada Pasien Obesitas Dengan Dekompensasi Gagal Jantung Akut Basah dan Hangat, Atrial Fibrilasi Respon Ventrikel Sedang, dan Gangguan Ginjal Akut: Sebuah Laporan Kasus - Oktaviani, Elma Mutiara; Farapti, Farapti; Mahmudiono, Trias; Rifqi, Niken Yunia (Universitas Airlangga, 2024)
Background: Obesity is caused by an imbalance between excessive energy intake and insufficient physical activity over a prolonged period. Obesity can increase the risk of metabolic syndrome, including heart failure. Severe heart failure can further elevate the risk of complications such as atrial fibrillation and acute kidney injury. In order to mitigate the exacerbation of heart failure severity in obese patients, it is imperative to institute a cardiovascular diet therapy employing the principles of adequate energy provision, low-fat content, and restricted protein intake within the framework of a Nutrition Care Process (NCP). Objective: To investigate the management of standard nutritional care in obese patients with acute decompensated heart failure, atrial fibrillation, and acute kidney injury through the administration of a cardiovascular diet. Methods: A case study was conducted in February 2023 on a patient at the University of Airlangga Infectious Disease Hospital, Surabaya. Results: The results of the clinical evaluation demonstrated an improvement in the patient's physical condition, as evidenced by the absence of dyspnea and stable vital signs within the normal range at the end of the intervention. The patient's food intake increased progressively, although some macronutrient targets were not fully met (<75%). Conclusion: The patient's condition showed significant improvement, as indicated by positive changes in physical/clinical monitoring. Additionally, there was an increase in food intake, although the target macronutrient intake was not fully achieved.